2017
DOI: 10.1038/srep39819
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis CBF3 and DELLAs positively regulate each other in response to low temperature

Abstract: The C-repeat binding factor (CBF) is crucial for regulation of cold response in higher plants. In Arabidopsis, the mechanism of CBF3-caused growth retardation is still unclear. Our present work shows that CBF3 shares the similar repression of bioactive gibberellin (GA) as well as upregulation of DELLA proteins with CBF1 and -2. Genetic analysis reveals that DELLAs play an essential role in growth reduction mediated by CBF1, -2, -3 genes. The in vivo and in vitro evidences demonstrate that GA2-oxidase 7 gene is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 79 publications
3
67
0
Order By: Relevance
“…) and jasmonic acid (Zhou et al . ). Thus, the dwarf phenotype in winter varieties growing at low temperature has been related to some of these factors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) and jasmonic acid (Zhou et al . ). Thus, the dwarf phenotype in winter varieties growing at low temperature has been related to some of these factors.…”
Section: Discussionmentioning
confidence: 97%
“…The known mechanisms underlying cold-induced signalling include post-transcriptional and post-translational key regulators, e.g. CBF/ DREB1 and phytohormones like ABA, auxin, gibberellic acid (GA; Kurepin et al 2013) and jasmonic acid (Zhou et al 2017). Thus, the dwarf phenotype in winter varieties growing at low temperature has been related to some of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Third, SlPIF4 directly bound to the G‐box of the CBF promoters in vitro and was associated with the promoters of the CBF genes in vivo (Figures d–g and S6). Finally, SlPIF4 promoted ABA and JA accumulation in tomato plants under cold stress (Figures and S7), which were positive regulators in cold stress (Wang et al , ), and enhanced the degradation of GA (Figures and S7), which was a negative regulator in cold tolerance (Achard et al , ; Zhou et al , ). Collectively, our results indicate that SlPIF4 works as a positive regulator of L‐R/FR‐induced cold tolerance in tomato plants that directly activates the transcription of CBF genes and regulates phytohormone homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, L‐R/FR failed to induce Fv/Fm values and CBF‐pathway gene ( CBF1 and COR413‐like ) expression in the SlGAI4‐ silenced plants (Figures b,c and S10b). Moreover, it has been reported that CBF and DELLAs positively regulate each other in response to low temperature in Arabidopsis (Achard et al , ; Zhou et al , ). Taken together, these results demonstrate that SlPIF4 also directly activated SlGAI4 , which acts as a positive regulator in the regulation of CBF1 gene expression and L‐R/FR‐induced cold tolerance in tomato plants during cold stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation